GE_GERICHTE P/17541/2013 vom 26. November 2015 - GE Cour de justice (2015)
PRÉSOMPTION D'INNOCENCE; MENACE(DROIT PÉNAL); FIXATION DE LA PEINE; PARTIE CIVILE; INDEMNITÉ(EN GÉNÉRAL); TORT MORAL | CEDH.6.2; CP.180; CP.47; CPP.126; CO.49; CPP.433.2